MEMÓRIAS E TRADIÇÕES ORIGINÁRIAS DO ANTIGO ISRAEL: Um estudo de Juízes 5. - SANTOS, LEIDE JANE SOARES DOS (2019)
This research focuses on the original memories of the people in ancient Israel contained in Jz 5. The most relevant themes of the pericope discussed start from the idea that this text comes from the Northern Kingdom of Israel and belongs to a collection of the "Saviors and Liberators" (Judges 3:7-12.15) of the people of Israel, which was later edited by the Deuteronomist. The original traditions and memories of the people highlighted by exegesis show the person of Deborah as a representation of the cult of female deities. We also note a possible origin of the worship of the Yahweh from "storms" and "earthquakes" from southern Canaan. Another relevant aspect is in the original list of tribes, as their mention in the text may indicate toponyms. The memory of the climax of the poem is in (Judges 5:19-22), where we perceived a conflict in the Valley of Jezrael caused by the destruction of city-states and the fall of Egypt, an empire that until then dominated the region. The oral memories, considered original of Old Israel, are located in the 10 BC century, a period prior to the development of the hebrew language.